Treatment outcome of extra-pulmonary tuberculosis in Finland: a cohort study - Liippo Kari; Ollgren Jukka; Holmström Pekka; Vasankari Tuula; Ruutu Petri (BMC Public Health, 2010)
Abstract Background We investigated the treatments given, the outcome and the patient- and treatment-system dependent factors affecting treatment outcome in a national two-year cohort of culture-verified extra-pulmonary tuberculosis cases in Finland. Methods Medical records of all cases in 1995 - 1996 were abstracted to assess treatment and outcome, using the European recommendations for outcome monitoring. For risk factor analysis, outcome was divided into three groups: favourable, death and other unfavourable. Predictors of unfavourable outcome were assessed in univariate and multivariate analysis. Results In the study cohort of 276 cases, 116 (42.0%) were men and 160 (58.0%) women. The mean age was 65.7 years. A favourable outcome was achieved in 157/276 (56.9%) cases, consisting of those cured (8.0%) and treatment completed (48.9%). Death was the outcome in 17.4% (48/276) cases, including cases not treated. Other unfavourable outcomes took place in 45 (16.3%) cases. Significant independent risk factors for death in multinomial logistic regression model were male sex, high age, immunosuppression, any other than a pulmonary specialty being responsible at the end of the treatment and other than standard combination of treatment. For other unfavourable treatment outcomes, significant risk factor was treatment with INH + RIF + EMB/SM. Deep site of TB was inversely associated with the risk of other unfavourable outcome. Conclusions The proportion of favourable outcome was far below the goal set by the WHO. Age and comorbidities, playing an important role in treatment success, are not available in routine outcome data. Therefore, comparisons between countries should be made in cohort analyses incorporating data on comorbidities.